Studi Pengaruh Waktu Pengadukan Pada Proses Pemurnian Garam Dengan Kombinasi Metode Hidroekstraksi Na – Zeolit - Ike Dayi Febriana, Annafiyah, Triyanti Irmiyana (Politeknik Negeri Madura, 2017)
Salt is one of the main commodities of the island of Madura especially in Sampang Regency. Salt is widely used for industrial, pharmaceutical, cosmetic, and household needs. Indonesian produce salt possess an average purity 90%, therefore salt refining is needed. Hidroextraction is one of salt refining method. In this experiment, hidroextraction was combined with Na – Zeolite as impurity settler. The aim of this research are to study about influence of stirring time and addition of Na – Zeolite in hidroextraction. The experiment were carried out from 4 to 12 minutes and used Na – Zeolite as much as 1 gr. The result of this experiment show that stirring time influenced the salinity. The highest salt content is produced at 4 minute stirring treatment that is equal to 99.9%. XRF analysis of zeolites showed increased levels of potassium (K) elements in zeolite solid.